Cultura organizacional y diversidad de género: análisis de la inequidad laboral en el Ban-Ecuador Chone - Barberán Moreira, Dallely Jaisury (2024)
The research examined the relationship between organizational culture and gender diversity at Ban-Ecuador Chone, specifically focusing on the workplace inequity experienced by women within the organization. The methodology is based on logical – deductive, mixed, exploratory methods that included tools such as interviews and surveys. Information was gathered regarding employees' perceptions of organizational culture and gender diversity, as well as exploring their experiences within the organization. The results indicate that the organizational culture at Ban-Ecuador Chone is influenced by traditional and gender-biased values that favor men at the expense of women. These values are reflected in the organizational structure and work practices, leading to a gender wage gap and a lack of professional development opportunities for women in the organization. The research concludes that Ban-Ecuador Chone needs to adopt specific measures to promote gender equality in its organizational culture, such as implementing inclusive policies and practices and providing employee training on gender and diversity issues. Additionally, it is suggested that ongoing monitoring of workplace practices be conducted, with adjustments made to ensure no gender discrimination within the organization.